0590 Usefulness Of Cardiac Parasympathetic Index In Cpap-treated Patients With Obstructive Sleep Apnea: A Preliminary Study. (12th April 2019) - Salsone, Maria; Marelli, Sara; Vescio, Basilio; Gambardella, Antonio; Quattrone, Aldo; Castelnuovo, Alessandra; Cuomo, Rossana; Ferini-Strambi, Luigi
Abstract: Introduction: Evidences demonstrate that Heart Rate Variability (HRV)-derived measurements such as cardiac autonomic indexes may be useful for accurately identifying patients with sleep disorders including Obstructive Sleep Apnea (OSA). In particular, cardiac parasympathetic index, a measure of diurnal and nocturnal parasympathetic activity can discriminate OSA patients from controls on an individual basis. However, the clinical usefulness of cardiac autonomic indexes after continuous positive airway pressure (CPAP) therapy remains unknown. The present study aimed to compare cardiac autonomic indexes (parasympathetic and sympathetic) at baseline and during a single night of CPAP therapy using a combined multimodal approach. Methods: This is a simultaneous HRV-polysomnographic (PSG) study including 10 patients with a clinical diagnosis of OSA. Patients underwent combined simultaneous recordings of polysomnography and autonomic detection in two consecutive time points, at baseline and during a single night of CPAP therapy. We measured the 24-hour HRV power spectral components during daytime and night-time periods, and analysed low-frequency (LF), high-frequency (HF) and night/day ratio for both LF (cardiac sympathetic index) and HF (cardiac parasympathetic) spectral components. Results: Mean age was 52.10± 7.75 year; moderate sleep apnea was determined in 5 patients and severe sleep apnea in the remaining 5. Mean AHI (Apnea-Hypopnea index) values were 44.1± 27.7 (baseline) and 7.77± 3.93 (after CPAP therapy). Compared to baseline evaluation, OSA patients showed cardiac parasympathetic index values significantly decreased during a single nocturnal-CPAP treatment (baseline: 2.41±0.72; CPAP:1.10±0.50) with a percentage of decrease equal to 53.7± 16.1. Cardiac sympathetic index had a lower mean percentage equal to 40.7± 23.7 with values at baseline equal to 1.94± 0.90 versus CPAP:1.06±0.51. A positive association was also found between the decrease of cardiac parasympathetic index values and severity of the disease. Conclusion: This study improves the knowledge on cardiac autonomic modulation during CPAP treatment of OSA patients. Our results demonstrate that cardiac autonomic indexes are significantly decreased after a single-night of CPAP therapy. Cardiac parasympathetic index better than sympathetic index was related to the decrease of AHI index after CPAP therapy. Support (If Any): none